2016
DOI: 10.5935/0103-5053.20160066
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Continuous Production of Solketal from the Acid-Catalyzed Reaction of Glycerol with Acetone

Abstract: A continuous-flow process at atmospheric pressure was designed for the conversion of glycerol to solketal, an oxygenated fuel additive, through the acid-catalyzed reaction of glycerol with acetone. Process optimization was performed by checking the influence of different variables on the conversion and selectivity. The variables examined were: residence time (12, 24, 60 and 120 min), catalyst type (Amberlyst-15 and K-10 Montmorillonite), catalyst loading (7, 3, and 1 g), reaction temperature (50, 40 and 30 ºC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…This issue has already been addressed in Section in which it was demonstrated that the use of dimethyl sulfoxide negatively affected the maximum reactants conversion. Oliveira et al also demonstrated that a higher glycerol conversion could be obtained when using dimethyl formamide as solvent than when using dimethyl sulfoxide under the same operating conditions (323 K and a 2.0 acetone to glycerol molar ratio). Hence, the use of solvents can simultaneously change the reaction kinetics and thermodynamic equilibrium since it affects the reactant and product concentrations, it modifies the interaction between species (accounted for in this work by the introduction of activity coefficients in the model), and it can change the species reactivity by solvation.…”
Section: Resultsmentioning
confidence: 95%
“…This issue has already been addressed in Section in which it was demonstrated that the use of dimethyl sulfoxide negatively affected the maximum reactants conversion. Oliveira et al also demonstrated that a higher glycerol conversion could be obtained when using dimethyl formamide as solvent than when using dimethyl sulfoxide under the same operating conditions (323 K and a 2.0 acetone to glycerol molar ratio). Hence, the use of solvents can simultaneously change the reaction kinetics and thermodynamic equilibrium since it affects the reactant and product concentrations, it modifies the interaction between species (accounted for in this work by the introduction of activity coefficients in the model), and it can change the species reactivity by solvation.…”
Section: Resultsmentioning
confidence: 95%
“…Overall, the most important properties of solid acid catalysts for the conversion glycerol to solketal production was the Brønsted acidity of solid acids [31]. The conversion of glycerol to solketal with resin catalysts has been carried out [32][33][34][35][36]. Table 3 summarizes the conversion of glycerol to solketal over resin catalysts.…”
Section: Glycerol-to-solketal Over Resin Catalystsmentioning
confidence: 99%
“…In particular, the reaction between glycerol and acetone leads to the formation of 2,2-dimethyl-1,3-dioxolane-4-yl methanol, known as solketal, a novel compound with interesting applications. Furthermore, 2,2-dimethyl-1,3dioxan-5-ol and water are also obtained as byproducts of this reaction (Scheme 1) [9,10]. Oliveira et al reported that solketal improves the octane number and prevents the formation of gum as a fuel additive.…”
Section: Introductionmentioning
confidence: 95%